2017
DOI: 10.1176/appi.ps.201600300
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experiences of Restrictive Interventions in Australia: Findings From the 2010 Australian Survey of Psychosis

Abstract: People with psychosis who experienced a greater number of restrictive interventions were less likely to find restrictions justified or beneficial. The cumulative effect of increased numbers of restrictions may also lead to worsening perceptions of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…This is supported in several previous studies where patients perceived seclusion to be a distinctly negative experience [3235]. Some recent studies suggest that patients can experience seclusion ambiguously—both beneficial and not—as having access to shelter or as being sent to prison [63, 64].…”
Section: Discussionsupporting
confidence: 70%
“…This is supported in several previous studies where patients perceived seclusion to be a distinctly negative experience [3235]. Some recent studies suggest that patients can experience seclusion ambiguously—both beneficial and not—as having access to shelter or as being sent to prison [63, 64].…”
Section: Discussionsupporting
confidence: 70%
“…Most studies (n=42) reported on restraint and seclusion techniques. The pooled prevalence for coercive interventions was 47.8% (95% CI 0.38 to 0.57) with high heterogeneity (I 2 100.0%) in 12 studies136–147 (online supplementary file 6).…”
Section: Resultsmentioning
confidence: 99%
“…Studies explored staff,148–157 patient147 158–165 and mixed groups’166–173 views and experiences of seclusion and restraint. Nine studies focused on the processes surrounding seclusion and restraint 136 137 174–180.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest papers reporting patient perspectives were published in 1996, exploring perspectives of forcibly medicated patients after discharge, and retrospective attitudes of patients to involuntary intramuscular medications . The four most recent papers also investigated patient and healthworker perspectives about coercion involving CR …”
Section: Resultsmentioning
confidence: 99%